PENERAPAN MEDIA GAMBAR DALAM MENINGKATKAN KEMAMPUAN MENULIS BERITA - Diah Nurwulandini; Suleman Suleman (Jurnal Ilmu Pendidikan UMGo, 2025)
This research aims to improve students’ ability to write news sentences through the use of picture media among fifth-grade students at SDN 11 Limboto, Gorontalo Regency. This research is a classroom action research involving 25 fifth-grade students of SDN 11 Limboto as the subjects. The data analysis techniques included data on teacher activities, student activities, and students’ speaking abilities. In the initial observation, only 7 students, or 28%, achieved mastery based on the minimum competency criterion (KKM) of 75. The results of the study in Cycle I showed that 17 students, or 68%, achieved mastery. In Cycle II, the number increased to 23 students, or 92%, indicating an improvement of 24%. Thus, it can be concluded that the use of picture media can enhance students’ writing skills in Indonesian language learning among fifth-grade students at SDN 11 Limboto.